Hemicomplemented Almost Distributive Lattices (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces the concept of condensed elements in an Almost Distributive Lattice(ADL) and explores their fundamental properties. It also presents the concept of hemicomplemented ADL and characterize of these ADLs using ideals,  congruences, and minimal prime $\LomD$-filters. Furthermore, a collection of equivalent criteria is established to determine when a hemicomplemented ADL qualifies as a quasicomplemented ADL.
Keywords: hemicomplemented ADL; condensed element; Almost Distributive Lattice